2022
DOI: 10.2196/37844
|View full text |Cite
|
Sign up to set email alerts
|

Cultural and Digital Health Literacy Appropriateness of App- and Web-Based Systems Designed for Pregnant Women With Gestational Diabetes Mellitus: Scoping Review

Abstract: Background The prevalence of women diagnosed with gestational diabetes mellitus (GDM) is increasing dramatically. Mobile technologies to enhance patient self-management offer many advantages for women diagnosed with GDM. However, to our knowledge, although mobile health (mHealth) and telemedicine systems for GDM management exist, evidence on their cultural and digital health literacy appropriateness levels is limited. Objective This review aimed to sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…When faced with uncertainty about the effectiveness of traditional practices and the lack of avenues available to obtain verified information, women from the current study were inclined to remain cautious and follow traditional advices from family and friends despite negative or no effects. In a recent systematic review examining culture appropriateness of digital tools designed for pregnant women with gestational diabetes mellitus, it was reported that only two out of 12 DHIs offer culturally appropriate content 44 . Accordingly, providing women with access to culturally adapted practices and information presents as a key component when designing DHIs with an education component.…”
Section: Discussionmentioning
confidence: 99%
“…When faced with uncertainty about the effectiveness of traditional practices and the lack of avenues available to obtain verified information, women from the current study were inclined to remain cautious and follow traditional advices from family and friends despite negative or no effects. In a recent systematic review examining culture appropriateness of digital tools designed for pregnant women with gestational diabetes mellitus, it was reported that only two out of 12 DHIs offer culturally appropriate content 44 . Accordingly, providing women with access to culturally adapted practices and information presents as a key component when designing DHIs with an education component.…”
Section: Discussionmentioning
confidence: 99%
“…Women with GDM were able to log their BGLs (with annotations, if desired) into the app manually or via a Bluetooth enabled glucometer, and the readings were then shared with their health care provider via While there is information in the literature pertaining to how health care providers experience digital models [11][12][13] and, more generally, how women experience having a diagnosis of GDM, 3 less is known about how models of care that incorporate a digital-solution are perceived by women engaging with them. 14,15 This article aims to describe women's experiences within a digitally-supported model of GDM care compared with a traditional model of GDM care.…”
Section: Digitally-supported Model Of Carementioning
confidence: 99%
“…While there is information in the literature pertaining to how health care providers experience digital models 11–13 and, more generally, how women experience having a diagnosis of GDM, 3 less is known about how models of care that incorporate a digital‐solution are perceived by women engaging with them 14,15 …”
Section: Introductionmentioning
confidence: 99%
“…The demand for healthcare services in developed economies has significantly increased over the past decade due to factors such as an aging population, the growing prevalence of chronic diseases, unhealthy lifestyles, and a progressive focus on physical and mental well‐being in modern societies (Birati et al, 2022). As a result, healthcare systems are facing higher workloads compounded by limited funding, particularly in the case of national health systems, and scarce human resources (Kumar et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of information technologies for the provision of remote medical services (e.g., telemedicine) currently plays a prominent role in the efficiency and sustainability of the healthcare systems and the improvement of the patient‐physician relationships (Birati et al, 2022; Birkmeyer et al, 2021). Within telemedicine, apps have experienced exponential growth in the last 5 years (Yan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%